Predicting revenue efficiency of the Portuguese artisanal dredge fishery using external factors - Ferreira, N. B.; Manuela Oliveira; JW; AMC (TBTI Symposium on European Small - Scale Fisheries and Global Linkages June 29-July 1, 2016)
Multidisciplinary scientific teams worldwide have tried, unsuccessfully, to explain the phytotoxins’ episodes. In the absence of an accurate system to predict these phenomena, and as a way to foresee compulsory closures for the Portuguese artisanal dredge fishery, the goal of this analysis is to characterize the relationship between phytotoxins’ episodes and several external factors such as: weather conditions, tourism and levels of revenue efficiency. Time series data characterising seawater temperature, air temperature, wave height, presence of phytotoxins, and levels of tourism will be used to model the relationship between revenue efficiency levels and the evolution of these external factors over the time. Data mining and Stochastic Frontier Analysis techniques will allow identifying appropriate models, able to predict the likelihood of revenue efficiency for given weather conditions, phytotoxins’ episodes and tourism occupancy rates.